Proxapertites from Walat Formation, Sukabumi, West Java, Indonesia - Rizki Satria Rachman; Winantris; Budi Muljana (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
Proxapertites have become one of the most significant indicators of ancient rock in Indonesia. Walat Formation is one of the oldest rocks exposed in Sukabumi, West Java, Indonesia. These Proxapertites have not been described in detail about their characteristics in previous studies, especially on Walat Formation. Therefore, knowing the characteristics of Proxapertites becomes interesting, especially in Walat Formation, which can be a reference for the characteristics of the late Eocene Proxapertites (37.8 - 33.9 million) in Indonesia. Acetolysis method was carried out for the preparation of pollen and spores; description and determination were carried out to see the characteristics of Proxapertites that present in Walat Formation. Result, there are three types of Proxapertites. Proxapertites operculatus have sizes 23 – 86 µ with average 40.5 (P) and 51.1 (E) µ, index PE 0,43 - 1, Peroblate – Subspheroidal – Oblate Spheroidal, Fine-Reticulate ornamentation, and Asymmetric Monosulcate aperture. Proxapertites cursus have sizes 23 – 86 µ with average 39.8 (P) and 49.8 (E) µ, index PE 0.51 - 1, Oblate – Subspheroidal – Oblate Spheroidal, Reticulate ornamentation, and Asymmetric Monosulcate aperture. Whereas Proxapertites psilatus have sizes 29 – 75 µ with average 42.3 (P) and 52.5 (E) µ, index PE 0.58 - 1, Oblate – Subspheroidal – Oblate Spheroidal, Psilate ornamentation, and Asymmetric Monosulcate aperture. These three Proxapertites can be distinguished by their type of ornamentation. Meanwhile, other aspects have similar characteristics and are affected by the appearance of individual pollen on the slide during preparation.